DVD, Blu-ray and Beyond
XIII, 244 p. 14 illus., 11 illus. in color.
Keywords: This book demonstrates, in contrast to statistics that show declining consumption of physical formats, that there has not been a mass shift towards purely digital media. Physical releases such as special editions, DVD box-sets and Blu-Rays are frequently promoted and sought out by consumers. And that past formats such as VHS, Laserdisc and HD-DVD make for sought-after collectible items. These trends are also found within particular genres and niche categories, such as documentary, education and independent film distribution. Through its case studies, this collection makes a distinctive and significant intervention in highlighting the ways in which the film industry has responded to rapidly changing markets. This volume, global in scope, will prove useful to those studying the distribution and exhibition of films, and the economics of the film industry around the world.